"Admiruję gorąco jej talent". Eliza Orzeszkowa czyta Konopnicką (Z badań nad epistolografią pisarki) = "I admire ardently her talent". Eliza Orzeszkowa reads Konopnicka (from the research on the writer's epistolography) - Sikora, Ireneusz (1952-2016) (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Eliza Pawłowska's and Maria Wasiłowska's school relationship would have been an insignificant in their biographies if she (the author of "Marta") had not become a writer and had not discovered Konopnicka as a poet (1878/1879). Orzeszkowa supported Konopnicka at the beginnings of her artistic career, defended from attacks of the conservative-catholic press.
Keywords: Orzeszkowa, Eliza (1841-1910) - twórczość; Konopnicka, Maria (1842-1910); epistolografia - 19 w.; liryka; małe formy narracyjne; biografia; samotność; emancypacja; kobiecość; epistolography; lyric poetry; short prose narratives; biography; loneliness; femininity; emancipation